Research on the coordinated relationship between human activities and ecosystem service value in the Arid Region, Northwestern China - Liu, Shiyao; Gao, Zhijian; Tao, Wanghai; Wang, Quanjiu; Su, Lijun; Sun, Yan; Shan, Yuyang; Qu, Zhi (Frontiers in Ecology and Evolution, 2024)
Arid and semi-arid regions encompass nearly 40% of the Earth's land surface and are characterized by extensive undeveloped land, scarce water resources, and fragile ecosystems. The arid northwestern China is a representative arid and semi-arid region.It has developed rapidly in recent years, leading to a significant increase in human activity. This increased activity has had a pronounced impact on the ecosystem, posing a major challenge to the environment. The close relationship between human activities and ecosystem service value (ESV) is crucial for the healthy development of both humans and ecosystems. However, the intricate nature of this relationship and the degree to which they are codependent remain unclear and require further investigation.This study investigates the impact of human activities on land use intensity (LUI) and degree of urbanization (URB). It comprehensively evaluates the spatial and temporal distribution of human activities and ESV, quantifying their coordination through coupling models. This work provides valuable insights and theoretical support for promoting the coordinated development of human activities and ESV. Overall, the LUI in the arid northwestern region decreased (from 0.485 in 2000 to 0.459 in 2020), while the URB increased (from 0.060 in 2000 to 0.087 in 2020). The ESV significantly increased, with a total growth of 556.58 billion yuan. In prefecture-level cities, the growth in ESV values ranges from 75.19 yuan/hm 2 to 10,062.49 yuan/hm 2 .The coupling coordination degree between ESV and LUI has changed over time, transitioning from uncoordinated development to coordinated development. In addition, the coordination between ESV and URB has evolved from uncoordinated development to transitional coordination. The level of coordination between human activities and ESV in provincial capital cities significantly influences the coordination in surrounding cities. This work provides effective development recommendations based on the ESV, LUI, and URB of different cities, and presents a development strategy for ecosystem service functions that is consistent with the 14 th Five-Year Plan and "Vision 2035" of each province. This study provides important insights into the relationship between human activities and ESV, and its findings can be used to guide coordinated and sustainable urban development.